Эффективность права в контексте правозащитной деятельности государства: теоретический аспект - Аракелян, Минас Рамзесович; Аракелян, Мінас Рамзесович; Arakeljan, Minas (My University, 2011)
The different concepts of efficiency of law. Carried out the study periods of legal science perspective the effectiveness of the law. Indicated on the specifics of the modern concept of the effectiveness of law, due to the folding of the country social and legal realities, and changing the type of law.
Аракелян М. Р. Эффективность права в контексте правозащитной деятельности государства: теоретический аспект / М. Р. Аракелян // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C.244-251.
Keywords: эффективность права; юридическая эффективность права; социальная эффективность права; критерии эффективности права; эффективность правовых норм; ефективність права; юридична ефективність права; соціальна ефективність права; ефективність правових норм; критерії ефективності права; law effectiveness; the legal effectiveness of the right; social efficiency of law; eligibility criteria of efficiency; the effectiveness of legal norms